Inhibition of nonsense-mediated mRNA decay (NMD) by a new chemical molecule reveals the dynamic of NMD factors in P-bodies - Durand, Sébastien (The Rockefeller University Press, 2007)
In mammals, nonsense-mediated mRNA decay (NMD) is a quality-control mechanism that degrades mRNA harboring a premature termination codon to prevent the synthesis of truncated proteins. To gain insight into the NMD mechanism, we identified NMD inhibitor 1 (NMDI 1) as a small molecule inhibitor of the NMD pathway. We characterized the mode of action of this compound and demonstrated that it acts upstream of hUPF1. NMDI 1 induced the loss of interactions between hSMG5 and hUPF1 and the stabilization of hyperphosphorylated isoforms of hUPF1. Incubation of cells with NMDI 1 allowed us to demonstrate that NMD factors and mRNAs subject to NMD transit through processing bodies (P-bodies), as is the case in yeast. The results suggest a model in which mRNA and NMD factors are sequentially recruited to P-bodies.